First report on the isolation of Trueperella abortisuis from companion animals. (August 2019) - Wickhorst, J.-P.; Hassan, A.A.; Sammra, O.; Alssahen, M.; Lämmler, C.; Prenger-Berninghoff, E.; Naggert, M.; Timke, M.; Rau, J.; Abdulmawjood, A.
Abstract: The present study gives a detailed phenotypic and genotypic characterization of three Trueperella abortisuis strains isolated from a ten year old male Hovawart dog with an abscess of anal sac, from urine of an eight year old European shorthair cat with urolithiasis and nephrolithiasis and from a 14 year old Maine Coon cat with a perianal abscess, respectively. All three strains could be identified phenotypically, by MALDI-TOF MS analysis and genotypically by sequencing the 16S rDNA and the molecular target genes gap and tuf . The present study gives a first description of T. abortisuis of this origin. Highlights: In present study three Trueperella abortisuis strains isolated from companion animals could be identified. This was performed phenotypically, by MALDI-TOF MS analysis and genotypically by sequencing the 16S rDNA and the molecular target genes gap and tuf . The present study gives a first description of T. abortisuis of this origin.